ANALISIS RASIO LIKUIDITAS DALAM MENILAI KINERJA KEUANGAN KOPERASI SIMPAN PINJAM (STUDI EMPIRIS PADA KOPERASI SENTRA DANA KABUPATEN CIANJUR) - Rosita, Siti; Setianegara, Raden Oky; Rachman, Fatwa Rubiar (Jurnal Nusa Akuntansi, 2024)
Financial reports are a very important source of information in order to assess financial performance from year to year. Providing information to parties who need financial report information that will be used for decision-making. This research was conducted to assess the financial performance of the Cianjur Regency Fund Center Cooperative from year to year, using financial reports in the form of a balance sheet and a profit and loss report for the period 2020–2021. One of the techniques used in analyzing financial reports is ratio analysis. In conducting this research, the author used ratio analysis, namely the liquidity ratio, which consists of the current ratio, quick ratio, and cash ratio. Based on the results of research conducted at the Cianjur Regency Fund Center Cooperative, from 2020 to 2021, there were changes that were not conducive to causing poor cooperative conditions. This is because the condition of the cooperative's financial performance has decreased.